Liberalism and Economic Growth: A Theoretical Exploration. (1st October 2016) - Ferguson, Peter
Abstract : This article explores how the liberal tradition of political thought has dealt with the prospect of limits to economic growth and how it should approach this issue in the future. Using Andrew Moravcsik's explanatory liberal theory, it finds that the commitment of governments to growth stems primarily from the aggregation of societal preferences for the social goods that growth produces. The arguments of liberal thinkers who have grappled with the issue of growth are then examined to gain a deeper theoretical understanding of the relationship between liberal democracy and growth. These include John Stuart Mill, for whom a non-growing economy was essential for overcoming the tension between liberty and equality; Ronald Dworkin, who argues that growth is a derivative means to further more fundamental ends; and Marcel Wissenburg, who suggests that it is legitimate for liberal democracies to limit the preference for growth if it risks undermining liberal norms and institutions. Using these theoretical insights, it is argued that environmental degradation, which is partly driven by growth, now threatens the fundamental liberal commitments of many liberals, including some forms of state neutralism, utilitarianism, inalienable individual rights and above all human autonomy. Therefore, liberal democratic states not only can, but must move towards a post-growth economy to secure these objectives into the future.